Mustang canyon - London, Jonathan, 1947-; San Souci, Daniel (Cambridge, MA : Candlewick Press, 2002)
A young mustang is separated from its mother when a plane sweeps over the canyon and the horses run from the noise.
Keywords: Mustang -- Juvenile fiction; Mustang -- Fiction; Animals -- Infancy -- Fiction; Horses -- Fiction